'It's like a drink you'd have before you go to a party': Analysis of a Vodka Cruiser advertising campaign. (12th April 2017) - Jones, Sandra C.; Francis, Kate L.; Gordon, Chloe S.
Abstract: Introduction and Aims: The aim of the present study was to explore young women's understandings of, and interactions with, an advertising campaign for a pre‐mixed alcohol product that appeared to be promoting pre‐drinking. This campaign was the subject of complaints to the Alcohol Advertising Review Board, revealing an inconsistency between the way the company responded to such complaints (arguing that the campaign does not encourage pre‐drinking) and the way it described the campaign in trade press (the pre‐drink enjoyed by the 'girls' while getting ready …). Design and Methods: Twelve focus groups were conducted with 72 young women, aged 15–25 years in Melbourne, Australia. These young women's interpretations of the messages communicated in this advertising campaign were analysed thematically. Results: The young women identified, without prompting, the main message of the campaign as being a reference to pre‐drinking. Most notably, the women saw the target audience as young (including underage) women. Discussion and Conclusions: Given that young women who drink are increasingly doing so at harmful levels, a marketing campaign, which is interpreted by the target audience to encourage pre‐drinking among young (including underage) women, appears to be inconsistent with the industry's own code for alcohol advertising. We renew the call for effective regulation of alcohol advertising to better protect young Australians. [Jones SC, Francis KL, Gordon CS. 'It's like a drink you'd have before you go to a party': Analysis of a Vodka Cruiser advertising campaign. Drug Alcohol Rev 2018;37:36–41]